Evaluation of serological response to foot-and-mouth disease vaccination in BLV infected cows - Puentes, Rodrigo (2016)
Background: Bovine Leukemia Virus (BLV) produces disorders on the immune system in naturally infected animals,which may counteract the development of immunity after vaccination. The aim of this study was to investigatewhether healthy and BLV infected cattle elicited similar humoral responses after foot and mouth disease (FMD)immunization. In a field study, 35 Holstein heifers were selected based on their BLV serological status and immunizedwith a single dose of a commercial bivalent oil-based FMD vaccine. Serum samples were collected at 0, 15, 60, 165and 300 days post vaccination (dpv).Results: Total anti-A24/Cruzeiro antibodies, IgM, IgG1, IgG2 titers and avidity index of specific antibodies weredetermined by ELISA. Although only marginally significant differences were found between groups in terms of totalantibodies, anti-FMD IgM and IgG1 titers were significantly lower in heifers infected with BLV at the 15 dpv (p < 0.01).Animals that became infected during the study did not show differences to the BLV negative group.Conclusions: Cattle infected with BLV at the time of immunization may elicit a low-magnitude serological response toa commercial Foot-and-mouth disease vaccine